Cell fusion mediated by interaction of a hybrid CD4.CD8 molecule with the human immunodeficiency virus type 1 envelope glycoprotein does occur after a long lag time. - Golding, H (1993)
Several domains of CD4 have been suggested to play a critical role in events that follow its binding to the human immunodeficiency virus type 1 (HIV-1) envelope glycoprotein (gp120-gp41). It has been reported previously that cells expressing a chimeric molecule consisting of the first 177 residues of human CD4 attached to residues from the hinge, transmembrane, and cytoplasmic domains of human CD8 did not form syncytia with HIV-1-infected cells (L. Poulin, L.A. Evans, S. Tang, A. Barboza, H. Legg, D.R. Littman, and J.A. Levy, J. Virol. 65: 4893-4901, 1991). In contrast, we found that the hybrid CD4.CD8 molecule expressed in human cells did render them susceptible to fusion with cells expressing HIV-1IIIB or HIV-1RF envelope glycoproteins encoded by vaccinia virus recombinants, but only after long lag times. The lag time of membrane fusion mediated by the hybrid CD4.CD8 molecule was fivefold longer than that for the wild-type CD4 molecule. However, the rate of binding to and the affinity of soluble gp120 for membrane-associated CD4.CD8 were the same as for CD4. Both molecules were laterally mobile, as determined by patching experiments. Coexpression of the CD4.CD8 chimera with wild-type CD4 did not lead to interference in fusion but had an additive effect. Therefore, the proximal membrane domains of CD4 play an important role in determining the kinetics of postbinding events leading to membrane fusion. We hypothesize that the long lag time is due to the inability of the CD4.CD8-gp120-gp41 complex to undergo the rapid conformational changes which occur during the fusion mediated by wild-type CD4.